الآثار المصرفية للأزمة المالية والاقتصادية العالمية على الجزائر - سليم مجلخ (My University, 2015)
ظهرت مع بداية القرن 21 أزمة مالية شبيهة بأزمة 1929، حيث نشأت وتطورت من أزمة عقار إلى أزمة مالية في الولايات المتحدة الأمريكية، ثم انتقلت وانتشرت في بقية دول العالم، بعد أن أصبحت أزمة اقتصادية أدت إلى ركود اقتصادي عالمي حاد، تسببت في أزمة بطالة خانقة، وقد اختلفت الآثار الناجمة عن هذه الأزمة باختلاف الدول من حيث متانة وقوة ارتباطها بالاقتصاد الأمريكي والعالمي، وقد انتقلت الأزمة إلى الجزائر كغيرها من دول العالم عبر قنوات غير مباشرة، واختلفت تداعياتها و أثارها باختلاف القطاعات والمجالات. ونحاول من خلال هذه الورقة البحثية تسليط الضوء على آثار الأزمة المالية والاقتصادية العالمية على الجهاز المصرفي الجزائري. Abstract: With the beginning of the 21st century, appears a financial crisis similar to the crisis of 1929. It has originated and evolved from the crisis of real estate into financial crisis in the United States, then moved and spread to the rest of the world countries. It led to a sharp global recession that a hard unemployment crisis. Its effects are different according to the countries differences in terms of its power and strength of association with the U.S. economy and the global economy. The crisis has moved to Algeria, through indirect channels, its repercussions and effects have varied according to the sector and domains. Through this research, we are trying to shed light on the effects of the global financial and economic crisis on the Algerian banking system.
Keywords: الأزمة المالية والاقتصادية العالمية، النظام المصرفي الجزائري، الآثار المصرفية، الإجراءات المتخذة